2018
DOI: 10.21059/buletinpeternak.v42i3.31998
|View full text |Cite
|
Sign up to set email alerts
|

The Use 3 of Banana Peel Meal (Musa paradisiaca) as Substitution of Corn in the Diets on Performance and Carcass Production of Hybrid Ducks

Abstract: This study was aimed to evaluate the utilization of banana peel meal as alternatives to substitution of corn in the diets based on the performance, carcass production, intestinal villi, the best type and utilization level of banana peel meal as corn substitution. A total of 105 male day old duck used in a completely randomized design (CRD), i.e. half of it (25%) and all of it (50%) replacing corn with banana peel meal PB= basal feed without banana peel meal; K25 and K50 = basal feed with Kepok banana peel meal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 20 publications
(22 reference statements)
0
6
0
5
Order By: Relevance
“…Shaddel-Tili, Eshratkhah, Kouzehgari, and Ghasemi-Sadabadi (2017) have reported that the process of absorption that occurs in the body of the livestock is influenced by the age, so that the feed given to livestock should be adjusted to the age. Fitroh, Wihandoyo, and Supadmo (2018) reported that due to the energy content, crude protein, crude fiber, crude fat, and minerals banana flour can meet the nutrient requirements in broiler. The different percentages of banana flour used can change the balance of feed nutrients (Fanimo & Oduronbi, 2006).…”
Section: Re Sultsmentioning
confidence: 99%
“…Shaddel-Tili, Eshratkhah, Kouzehgari, and Ghasemi-Sadabadi (2017) have reported that the process of absorption that occurs in the body of the livestock is influenced by the age, so that the feed given to livestock should be adjusted to the age. Fitroh, Wihandoyo, and Supadmo (2018) reported that due to the energy content, crude protein, crude fiber, crude fat, and minerals banana flour can meet the nutrient requirements in broiler. The different percentages of banana flour used can change the balance of feed nutrients (Fanimo & Oduronbi, 2006).…”
Section: Re Sultsmentioning
confidence: 99%
“…Kulit pisang merupakan salah satu limbah pertanian yang dapat dijadikan sebagai pakan ternak, kandungan protein kasar mencapai 8%, lemak kasar 6,2% (Wadhwa and Bakshi, 2013), lemak kasar 2,52%, serat kasar 18,71% (Koni, 2013); Ca 0,27 dan pospor 0,26% (Fitroh et al, 2018). Selain kandungan nutrien kulit pisang juga mengandung tanin sebesar 4,97% (Hudiansyah et al, 2015).…”
Section: Pendahuluanunclassified
“…Kepok banana peel weight is about 25 -40% of the weight of bananas (Koni, Bale-Therik, and Kale, 2013;Wadhwa, Bakshi, and Makkar, 2015). Banana peels (Musa paradisiaca normalis) contain crude protein 3.6 -8% (Koni, 2013;(Hudiansyah, Sunarti, and Sukamto, 2015;Wadhwa, Bakshi, and Makkar, 2015), crude fat from 2.52 -6.2% (Koni, 2013;Wadhwa, Bakshi, and Makkar, 2015), crude fiber 18.71% (Koni, 2013), 37.64% (Hudiansyah Sunarti, and Sukamto, 2015), Ca 0.27%, and phosphorus 0.26% (Fitroh, Wihandoyo, and Supadmo, 2018) Kepok banana peels can be used as much as 7.5% in broiler feed (Koni Bale-Therik and Kale, 2013); 20% (Widjastuti and Hernawan, 2012) and 10% as corn substitute in broiler rations (Duwa et al, 2014), while Kepok banana peels fermented with Rhizopus oligosporus can be used up to 10% in broiler rations (Koni, Bale-Therik and Kale, 2013).…”
Section: Introductionmentioning
confidence: 99%